Investigating the development of production-economic relations in the agricultural sector of Iran - Babapour, Mojahed; Seyednourani, Seyedmohammadreza; Isa Aliyev (Technium Social Sciences Journal, 2020)
The agricultural sector in developing countries is the main engine of economic growth and development. Developing countries can go to their agricultural sector to overcome the crisis of underdevelopment, and while trying to expand agricultural production, they are thinking of combining this sector with advanced technologies in order to make their products more efficient. Due to its extensive connections with other economic sectors, this sector can provide the ground for wealth production, market creation, currency exchange and industry growth with its growth. The purpose of this study was to investigate the development of production-economic relations in the agricultural sector of Iran. In this regard, the impact of development policy and growth of the agricultural sector on employment, total economic output and other economic sectors has been evaluated. The methodology of this research has been done with the approach of input and output table and social accounting matrix. The analysis is based on the approach of technical coefficients, Leontief coefficients, backward and forward linkages and employment coefficients. Results show that there are strong linkages between the "Agriculture and Horticulture" and "Livestock and Fisheries" sectors and the "Agriculture and Horticulture" sector has a strong and rapid impact on the final demand of the "Chemical Industries" sector as well as the "Livestock and "Fishing" has had a strong and rapid impact on the final demand of the "Livestock and Fisheries" sector. The backward and forward linkages of the agriculture section in the economy are at a moderate level and this sector has a high coefficient and potential in job creation and in line with strategies to reduce unemployment with lower investment has the ability to create high employment.